CADAVERIC MEASUREMENT AND ANALYSIS OF INTERSCALENE TRIANGLE AND COSTO-CLAVICULAR SPACES IN RELATION TO THORACIC OUTLET SYNDROME - Subhramoy Chaudhury; Anasuya Ghosh (Asociación Argentina de Anatomía Clínica, 2020)
Objectives: Thoracic outlet syndrome (TOS) is an upper extremity disorder resulting from compression of brachial plexus structures and subclavian vessels within thoracic outlet region at any of the three primary sites- interscalene triangle, costoclavicular space and retro-pectoralis minor space. This study focused on detailed anatomic exploration and measurement of normal anatomic variability within interscalene triangle and costoclavicular space. Material and Method:  We examined 49 cadavers (22 male and 27 female) and dissected both sides to explore and examine 98 dissected areas. We measured the base width, height, angle within interscalene triangle and the vertical distance within costoclavicular space. We also calculated the area of interscalene triangle. Results: The mean values of base width, height, interscalene angulation of interscalene triangle and height of costoclavular space was 10.18±4.31 mm, 45.19±0.07mm, 10.85±0.06 degrees and 10.22±0.07 mm respectively. The mean area of interscalene triangle was 214.82±5.22sqmm. Conclusion: We have found clinically significant differences between the interscalene and costiclavicular space vertical heights; the height of costoclavicular space was clinically significantly lower than the interscalene space (p< 0.001). No clinical significant difference was found between male and female measurements. These ranges of dataset could be useful for planning treatment approaches in TOS.